Evaluation of Ecopreneurship Business Sustainability in the Context of the Digital Economy - Dudhat, Amitkumar; Dolan, Ellen (Startupreneur Business Digital (SABDA Journal), 2025)
The rapid growth of the digital economy has significantly transformed the business landscape, providing new opportunities for ecopreneurship, a business model that integrates environmental sustainability with entrepreneurial practices. Facing increasingly significant environmental challenges, ecopreneurs leverage digital technologies to address sustainability issues while maintaining profitability. This paper aims to evaluate the sustainability of ecopreneurship businesses in the context of the digital economy, focusing on the role of digital technology in supporting environmentally friendly practices and expanding business operations. A qualitative research approach is used, involving case studies of successful ecopreneurial businesses and interviews with industry experts to gain insights into the integration of digital technology into sustainable business practices. The findings show that digital technologies such as e-commerce platforms, cloud computing, and data analytics have a positive im- pact on ecopreneurs, such as improving operational efficiency, expanding market reach, and reducing environmental footprints. However, challenges remain, including high initial costs for technology adoption, data privacy issues, and the balance between innovation and environmental impact. The sustainability of ecopreneurship businesses in the digital economy depends on the ability to integrate digital innovation with sustainable business models, adapt to technological advancements, and address environmental and ethical issues related to digitalization. This paper provides valuable insights into how ecopreneurs can tackle these challenges to achieve long-term sustainability.